2006
DOI: 10.1890/1051-0761(2006)016[1461:rsageg]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Shading and Groundwater Enhance Growth Potential for Smallmouth Bass in Ozark Streams

Abstract: Abstract. Moderation of stream temperatures by riparian shading and groundwater are known to promote growth and survival of salmonid fishes, but effects of riparian shade and groundwater on to be growth of warmwater stream fishes are poorly understood or assumed to be negligible. We used stream temperature models to relate shading from riparian vegetation and groundwater inflow to summer water temperatures in Missouri Ozark streams and evaluated effects of summer water temperatures on smallmouth bass, Micropte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 40 publications
3
83
0
Order By: Relevance
“…The mining-derived sulfates originating from Blue Spring may also affect methylation rates, as may stream temperature. The latter may also influence Hg concentrations in fish through effects on feeding and growth rates (e.g., Norstrom et al, 1976;Whitledge et al, 2006;Ward et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mining-derived sulfates originating from Blue Spring may also affect methylation rates, as may stream temperature. The latter may also influence Hg concentrations in fish through effects on feeding and growth rates (e.g., Norstrom et al, 1976;Whitledge et al, 2006;Ward et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mercury concentrations (as MeHg) tend to increase with age and body size in upper trophic level fishes (Wiener et al, 2003(Wiener et al, , 2006McIntyre and Beauchamp, 2007), but size-concentration relations have not been evident in Ozark smallmouth . These relations can also be obscured by growth dilution (e.g., Ward et al, 2009), and growth rates can be influenced by the temperature stability afforded by springs (Whitledge et al, 2006). HgT concentrations also tend to be lower in smallmouth from streams that drain historical lead-zinc mining areas than elsewhere in southern Missouri (e.g., .…”
Section: Introductionmentioning
confidence: 99%
“…Stream shading percentages were estimated through on-site evaluation. Components of SSTEMP, which aptly model individual stream reaches, and the more detailed SNTEMP, which models a complex network of stream reaches, have been used to evaluate the effect of altered flow regimes, stream widths, and riparian shading on water temperatures in a Colorado trout (Oncorhynchus mykiss and Salmo trutta) stream (Bartholow, 1991), evaluate the importance of groundwater and riparian shading on adequate bass (Micropterus dolomieu) habitat in Ozark streams (Whitledge et al, 2006), and determine the influence of stream shading in maintaining summer temperatures in a brook trout stream (Pajak, 1992). Additionally, Gaffield et al (2005) used an adapted version of SNTEMP, to illustrate the overall importance of groundwater and riparian shading as controls to summer temperature in small Midwestern streams while emphasizing the significance of temperature models in facilitating watershed management decisions.…”
Section: Stream Temperaturementioning
confidence: 99%
“…Human activities which alter land cover within a watershed therefore have the ability to impact the thermal regime of stream ecosystems for brook charr (Dunne & Leopold, 1978;Bartholic et al, 1983;Wang et al, 2003;Gaffield et al, 2005;Wang et al, 2006;Whitledge et al, 2006). Under natural conditions, the groundwater system is constantly discharging (outflow to lakes, streams, and wetlands) and recharging (inflow from precipitation, loss to surface water bodies) to maintain equilibrium; however, this natural equilibrium changes when groundwater is withdrawn from the aquifer or land cover alterations reduce recharge rates to the groundwater aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…Macdonald et al, 2003). In some cases the effects of variable harvesting practices have also been evaluated Gomi et al, 2006) and recent efforts have attempted to model observed differences in the spatial and temporal distribution of temperatures using process-based models (Rutherford et al, 1997;Chen et al, 1998a;Rutherford et al, 2004;Gomi et al, 2006;Whitledge et al, 2006;Cox and Bolte, 2007;Westhoff et al, 2007) with the aim of predicting the effects of future changes in land use (Rutherford et al, 1997;Chen et al, 1998b;Whitledge et al, 2006).…”
Section: Introductionmentioning
confidence: 99%